Propuesta de una tecnología para reducir carga contaminante de los efluentes líquidos de una curtiembre en el distrito del porvenir. - Ganoza García, Juan Alberto (2010)
In this report a proposal for a technology is studied to reduce the pollutant load of liquid effluent from a tannery in the district El Porvenir characterized by its high content of suspended solids, the presence of sulfides and Cr (III). The same people who were determined by analysis of effluents liming, tanning and final effluents. the different stages of leather tanning process, which takes place in the Tannery del Porvenir, allowing locate information within the field and study sections is further described in general. The proposed method is a physical-chemical treatment in which FeCl3 is used as a flocculant and Ca (OH) 2 as a coagulant and pH stabilizer. The effectiveness of treatment is reflected in the reduction of the values of total solids, DBOs, COD, trivalent chromium, sodium sulfide, the same as before treatment exceed the maximum permissible limits.